STUDI DISKRIPTIF PERUBAHAN BUDAYA ORGANISASI KEPERAWATAN - Teguh Anindito (Jurnal Surya Muda, 2021)
A good organization also has good order. Regularity is inherent and becomes a habit that unwittingly becomes a culture, thus distinguishing it from other groups. Muhammadiyah Kendal Islamic Hospital experienced ups and downs during the leadership of the institution's management. The new leadership brings change, the bad culture of the organization must be changed, especially in the field of nursing. Nursing in the hospital is the driving force of organizational life. The purpose of this study is to see the extent to which organizational culture changes to the work culture of nurses after a change in leadership. Data retrieval using descriptive method. Data were taken from RSI nurses totaling 76 nurses Based on the inclusion and exclusion criteria, the researcher only took 33 people who had had a minimum of one year of service, and experienced a change in leadership. Data processing. This data is processed in manual by using excel programe. Of the 33 nurses, 50% of the leadership's attention is good, while 50% is less. This condition illustrates that nurses group need more intention supervision. From the data above, it can be concluded that caused organizational changes, performance has not been maximized, coordination has not been maximized and routine, the new work culture has not been fully formed.